Pengaruh Elektromagnetik Exchange pada Charge-Radius Isotop Ca: Electromagnetic Exchange Effect in Charge-radii Ca-Isotopes - Nugraha, Alpi Mahisha; Nurullaeli (Jurnal Jejaring Matematika dan Sains, 2021)
The charge-radii nuclei is distribution of the coulomb effect but respectively isn’t distribution of proton due to affected by the scattering of electrons in nuclei and is an observable quantity in laboratory. In this research, we use RMF model in Ca-isotopes with and without electromagnetic exchange form, and be compared with experiment from IAEA. With a fairly good accuracy (above 99%) on the binding energy, it shows that this model is powerful. Unfortunately, at the correlation to charge-radius, even with good enough accuracy (above 97%), it still doesn't show electromagnetic exchange corellation. An analysis of all RMF forms is needed to get a better correlation to the charge-radii nuclei clearly here.